Co-removal of CO2 and particulate matter from industrial flue gas by connecting an ammonia scrubber and a granular bed filter. (1st June 2020) - Sun, Wenqiang; Shao, Yixin; Zhao, Liang; Wang, Qiang
Abstract: Industry emits huge amount of CO2 and particulate matter (PM) in the form of flue gas. In the context of climate change mitigation and air pollution control, preventing and reducing CO2 and PM from industrial flue gas are of great significance. CO2 and PM are currently removed separately, which puts a burden on environmental investment and land occupancy. In this work, a novel co-removal system is designed for simultaneously and synergistically removing CO2 and PM from industrial flue gas, by connecting an ammonia scrubber (AS) and a granular bed filter (GBF) in series. To validate the concept, an experimental apparatus was built, and the parameters influencing the CO2 and PM removal efficiencies in the AS, GBF and the whole system are investigated. Results show the CO2 and PM removal efficiencies of the co-removal system are 89.46% and 99.76%, respectively, and are higher than that of each single subsystem. In addition, the optimal operating conditions of the co-removal system are determined, including ammonia flow rate, ammonia concentration, filter materials filled in the GBF upper layer, filter materials' size, and the GBF upper layer height. In addition, the influence and sensitivity of their variations on the system removal efficiency are analysed. Graphical abstract: Image 100 Highlights: A co-removal system of CO2 and PM from industrial flue gas is designed. The co-removal system combines an ammonia scrubber and a granular bed filter in series. The operational parameters of the co-removal system are experimentally investigated. The optimal operating conditions for the co-removal apparatus are determined.